Analysis and Application of Vibration Damping Hole in Tunnel Working Face Based on Grey Correlation Analysis. (27th June 2022) - Duan, Baofu; Zhengxin, Zhang; Chunwu, Zhang; Sun, Zongjun
Abstract : In the process of tunnel blasting construction, certain vibration hazards will be caused to adjacent buildings. Therefore, it is necessary to explore feasible vibration reduction measures in the construction process. Combined with field measurement and numerical calculation, the law of vibration reduction effect of vibration reduction holes in the blasting construction of subway tunnels is analyzed. The gray correlation theory is used to determine the influence degree of vibration reduction hole parameters on the vibration reduction effect; each parameter is clarified, and the primary and secondary relationship of each parameter in the vibration reduction effect is clarified. Among them, the effect of damping hole spacing is particularly obvious. Combined with numerical calculation and comprehensive analysis of on-site construction effects, it is found that during the construction process, the distance between the vibration damping holes is 120 mm, the distance between the vibration damping holes and the explosion source is 2000 mm, the diameter of the vibration damping holes is more than 120 mm, the depth of the vibration damping holes is 1200–1500 mm, and double-row vibration-damping hole spacing is 50–100 mm, which can achieve a better vibration-damping effect. The research results will provide a reference vibration reduction technology for the blasting construction of urban shallow tunnels and have certain reference value and guiding significance for the blasting scheme design and vibration control of similar projects.